Renal arteriolosclerosis impact on clinicopathological features and outcomes of idiopathic membranous nephropathy: a retrospective cohort analysis - Jiang, Rui; Li, Li; Yan, Yunfei; Li, Hucai; Yu, Ruizhi; Huang, Yang; Wang, Lixin (Frontiers in Medicine, 2025)
BackgroundTo investigate the clinicopathological features and prognostic factors of idiopathic membranous nephropathy (IMN) patients with renal arteriolosclerosis, providing evidence for individualized clinical management.MethodsA retrospective analysis was conducted on 597 biopsy-confirmed IMN patients at Guangdong Provincial Hospital of Chinese Medicine from January 1, 2012, to December 31, 2022. Patients were stratified into two groups based on the presence of renal arteriolosclerosis. Clinical and pathological characteristics were compared between groups. Kaplan–Meier curves were used to assess cumulative renal remission rates, and Cox regression analysis was performed to identify risk factors for composite endpoint events in IMN patients with arteriolosclerosis.ResultsIn a cohort of 597 IMN patients (55.6% male), significant baseline differences were observed in Serum Sodium, triglycerides, membranous nephropathy (MN) stage, mesangial proliferation, interstitial fibrosis, and IgG deposition between the arteriolosclerosis and non-arteriolosclerosis groups (p < 0.05). Kaplan–Meier analysis demonstrated markedly lower renal survival in the arteriolosclerosis group (Log-rank χ2 = 8.296, p = 0.004). Multivariate Cox regression identified age (HR = 1.022, 95% CI 1.003–1.042; p = 0.022), serum creatinine (SCr) (HR = 1.010, 95% CI 1.002–1.018; p = 0.017), IgM 3 + deposition (HR = 4.718, 95% CI 1.003–1.042; p < 0.001), and interstitial fibrosis (HR > 1, p < 0.05) as independent risk factors for composite endpoint events, Compared to their respective reference groups, C1q (3+) and tubular atrophy (≥50%) have a protective effect against adverse renal outcomes (HR < 1, p < 0.05).ConclusionRenal arteriolosclerosis portends poorer prognosis in IMN, with distinct clinicopathological features and accelerated renal function decline. Age, elevated creatinine, intense immune complex deposition, and advanced tubular-interstitial damage represent critical risk markers, highlighting the need for early vascular assessment and histology-guided risk stratification in this population.